The influence of Mat Pilates associated with perineal contraction in the female sexual response - Oliveira, Maria Eunice Chagas; Oliveira, Fernanda Gonçalves de; Araújo, Nazete dos Santos; Nunes, Erica Feio Carneiro; Rodrigues, Cibele Nazaré Câmara (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: The Pilates Method is a program of physical and mental training that involves the whole body, aiming at the gain of muscular strength, mainly of the central region, formed by the abdominal muscles, the spine and the pelvic floor muscles (PFM). The PFM responds to sexual stimulation, with increased local blood circulation and involuntary contractions during orgasm. The training of this musculature assists in the female sexual function. Objective: To evaluate the influence of Pilates Mat associated with perineal contraction in the female sexual response. Method: Uncontrolled clinical trial in which participated twelve women between 20 and 50 years old, who performed Mat Pilates classes associated with perineal exercises, three times a week. The sexual response was evaluated through the Female Sexual Function Index (FSFI) and the contraction capacity of PFM through the Functional Evaluation of the Pelvic Floor (FEPF) before and after 21 sessions. Results: Given the proposed treatment, the FSFI responded positively (0.0099), with an improvement in the median and interquartile range that initially was 25.6 ± 5.4 and increased to 28.4 ± 1.2. The Functional Evaluation of the Pelvic Floor (FEPF) also achieved significant improvement (p= 0.0077), increased from the initial median and interquartile range of 2 ± 1.5 to 4 ± 1. Conclusion: Mat Pilates provides encouraging results, and its use is relevant to promote improved sexual response and strength gain of the pelvic floor muscle.